The Effects of Customer Satisfaction on Intentions To Stay At MSME In The Covid-19 Endemic In Indonesia - Agustin Riyan Pratiwi Pratiwi; Fikri Ardian Ardian (International Journal Business and Entrepreneurship, 2024)
This study aims to examine the consequences of customer satisfaction on the intention to stay at MSMEs during the Covid-19 endemic in Indonesia. The sample was determined by the Random Cluster Sampling Method with a sample size of 400 respondents. The results revealed that the value of the perceive price for customer satisfaction has a p-value higher than the lowest average value. The Product Quality for customer satisfaction has a greater p-value than the lowest average value. The value of Service Quality towards customer satisfaction has a smaller p-value than the lowest average value. Customer satisfaction valued by word of mouth has a smaller p-value than the lowest average value. Customer satisfaction towards intention to stay has a smaller p-value than the lowest average value.